1982
DOI: 10.1038/300143a0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of activation of a human oncogene

Abstract: The oncogene of the human EJ bladder carcinoma cell lines arose via alteration of a cellular proto-oncogene. Experiments are presented that localize the genetic lesion that led to activation of the oncogene. The lesion has no affect on levels of expression of the oncogene. Instead, it affects the structure of the oncogene-encoded protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
557
2
10

Year Published

1984
1984
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,304 publications
(590 citation statements)
references
References 41 publications
15
557
2
10
Order By: Relevance
“…p21 proteins are ubiquitously expressed and are thought to play an important role in the proliferation of normal cells (13). Although overexpression of normal p21 proteins can induce morphologic transformation of established rodent cells, ras genes that encode certain missense mutations induce these changes with much greater efficiency (15,21). ras genes with such activating mutations have been identified as the cellular transforming genes of a wide variety of tumors in humans and animals and also as the viral oncogenes of several acute transforming retroviruses (reviewed in reference 2).…”
mentioning
confidence: 99%
“…p21 proteins are ubiquitously expressed and are thought to play an important role in the proliferation of normal cells (13). Although overexpression of normal p21 proteins can induce morphologic transformation of established rodent cells, ras genes that encode certain missense mutations induce these changes with much greater efficiency (15,21). ras genes with such activating mutations have been identified as the cellular transforming genes of a wide variety of tumors in humans and animals and also as the viral oncogenes of several acute transforming retroviruses (reviewed in reference 2).…”
mentioning
confidence: 99%
“…The single base change at position 35, in the c-ras' gene recovered by transfection of DNA from the T24 human bladder carcinoma line into NIH 3T3 cells provides the first direct evidence of the involvement of point mutation in human neoplasia (Reddy et al, 1982;Tabin et al, 1982;Taparowsky et al, 1982). The guanosine to thymidine mutation which changes amino acid 12 from glycine to valine confers on the gene product transforming properties not possessed by the unaltered gene product.…”
Section: Genetic Change In the Cancer Cellmentioning
confidence: 98%
“…Coding sequence mutations, causing amino acid substitutions at critical positions within the p21 product, as well as truncation of a putative 5' exon, have been reported to represent critical steps in the Ha-ras activation process [2][3][4][5][6]. Recent microinjection experiments have also demonstrated that overdosage of the normal Ha-ras product may be sufficient to induce cell transformation [7] and, with respect to norma1 tissues, increased amounts of p21 have been found in tumor cells of primary breast carcinomas and have been shown to correlate with other clinica1 and prognostic variables [8, 91. These circumstances, and others as well, greatly support the hypothesis of an involvement of the Ha-ras proto-oncogene in tumorigenesis, although its precise role in this process still remains to be defined [lo].…”
Section: Introductionmentioning
confidence: 99%